National Minority Education in Croatia - Mesić, Milan; Baranović, Branislava (2005)
Croatia seems to be a fairly good example to illustrate the complexity and controversies encountered when dealing with the education of national ethnic minorities. National minority rights, including education, are far more complicated and sensitive projects in a transitional society - especially in countries immediately after a war or after severe interethnic conflicts (which sometimes escalated to "ethnic cleansing" as in Croatia and Bosnia and Herzegovina) - in comparison with well-settled, advanced democracies with elaborated human rights and with a "historical distance" towards previous wars and ethnic conflicts. In Croatia we can distinguish between "historical or autochtonous national minorities", some of which could be called "imperial", and the so-called "new minorities". Sooner or later we can expect the formation of immigrant minorities together with the rise of labour immigration. Special education for minorities is a thorny agenda, which on the one hand involves "real demands" (the European Charter) by vivid cultural communities with a developed collective identity and on the other, the readiness of a government to adopt these cultural (educational) demands as legitimate ones. The juridical-formal and public-political recognition of minorities and their rights to social and cultural equality is only the beginning and not the end in the process of comprehensive reconstruction of both a society and its educational system towards intercultural negotiations and multicultural perspectives. If minority education reduces itself to mechanically added special, minority related contents with no real interaction with the common majority education, it may only lead to further alienation of that minority from mainstream society and even to its stigmatisation. The social and cultural integration of a national minority into an open multicultural society depends not only on the willingness of a dominant ethnic group to recognise its equal cultural rights, but also depends on the political culture and readiness of a given minority to integrate into a culturally pluralistic society and accept the equality of others ("minority paradox"). As a final conclusion, the formally equal approach to different cultural communities may provoke new issues and jeopardise even a sincere attempt to promote the minority cause in education or in other fields. A fair and just education of national minorities in a society opening itself up to multiculturalist prospects can only be the result of a dynamic process of negotiations between a majority and a minority group (or groups) based on mutual recognition.
Nedostaje podatak o stranicama. (admin.)
Projekt MZOS
Projekt MZOS
ENG